Answer:
(g+ h) (-3) = 4
Explanation:
g(x) = 8x - 3
h(x) = 3x² - 2x - 2
To find (g+ h) (-3) we must first find
(g+ h) (x)
To find (g+ h) (x) add g(x) to h(x)
That's
(g+ h) (x) = 8x - 3 + 3x² - 2x - 2
(g+ h) (x) = 3x² - 2x + 8x - 3 - 2
(g+ h) (x) = 3x² + 6x - 5
To find (g+ h) (-3) substitute the value of x that's - 3 into (g+ h) (x) that's for every x in (g+ h) (x) replace it with - 3
We have
(g+ h) (-3) = 3(-3)² + 6(-3) - 5
= 3(9) - 18 - 5
= 27 - 18 - 5
We have the final answer as
(g+ h) (-3) = 4
Hope this helps you